Sayyid Amir Ali (Telaah terhadap Ide Pembaruan Islam) - Rahmawati Rahmawati (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2009)
Although Ameer Ali's thinking was regarded as apologetic about Islam, he was indeed able to perform high defence towards Islam and show Islam as a rasional religion to the world. Ameer Ali explains that the retreat of Islamic people is due to thinks and the close up ijtihad's door. They obey what the nineth century ulama said, which is in fact not suitable to be applied in modern century. It is considered that Islamic people seem to be no longer value their mind, which is indeed very valuable from the persfective of islamic teaching. Therefore, Islamic people are encouraged to deepen their knowledge as much as possible. According to Ameer Ali, Islam is the religion which is in the front line to the improvement of scince and knowledge.